1986
DOI: 10.1111/j.1745-4557.1986.tb00769.x
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Restructuring of Beef

Abstract: Restructured steaks munufactured by two comminution methods from prerigor electrically stimulated (PES) beef nonstimulated counterparts(NES) and postrigor non-electrically stimulated (C) samples were compared. After frozen storage for 0,14, and 42 days, samples were subjectively evaluated for appearance and palatability traits. Objective measurements included Hunter Color, TBA, Kramer, and Instron values. Electrical stimulation reduced peak force but did not consistently improve sensory panel scores. Comminuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

1986
1986
1988
1988

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 7 publications
2
9
0
Order By: Relevance
“…Their prerigor steaks were less desirable, when considering tenderness, texture, flavor and overall palatability, than the restructured counterparts from postrigor beef. Restructured prerigor beef steaks (Marriott et al 1985) and pork chops (Marriott et al 1983) were not different (P> 0.05) in tenderness and other sensory attributes when compared to postrigor counterparts. Although different responses have been noted with the use of prerigor beef muscle, Kastner (1982) has suggested that prerigor beef offers functional advantages over postrigor muscle.…”
Section: Introductionmentioning
confidence: 81%
“…Their prerigor steaks were less desirable, when considering tenderness, texture, flavor and overall palatability, than the restructured counterparts from postrigor beef. Restructured prerigor beef steaks (Marriott et al 1985) and pork chops (Marriott et al 1983) were not different (P> 0.05) in tenderness and other sensory attributes when compared to postrigor counterparts. Although different responses have been noted with the use of prerigor beef muscle, Kastner (1982) has suggested that prerigor beef offers functional advantages over postrigor muscle.…”
Section: Introductionmentioning
confidence: 81%
“…chucks and rounds) with higher grading boneless cuts such as plates, flanks, chucks and rounds. Hot boned beef was incorporated in formulations evaluated by Pepper and Schmidt (1975), Solomon and Schmidt (1980) and Marriott et al (1985) while Furumoto and Stadelman (1980) evaluated hot boned pork, chicken, turkey and beef.…”
Section: Introductionmentioning
confidence: 99%
“…Lower scores at 70 days were attributable to the effect of NaCl and storage time on color stability. Schwartz and Mandigo (1976) and Marriott et al (1983Marriott et al ( , 1985a have previously demonstrated that NaCl can enhance color degradation during frozen storage. Data in Table 1 suggest that spleen pulp can enhance color development during frozen storage for a short period but offers no benefit toward color preservation during prolonged storage.…”
Section: Resultsmentioning
confidence: 99%
“…Recent research in our laboratories has revealed a potential opportunity to reduce production costs and expedite product movement through accelerated manufacture of restructured muscle foods from prerigor muscle (Marriott et al 1983;Marriott et al 1985a). Yet, an adjunct with demonstrated ability to improve texture and tenderness such as MSS (spleen pulp) is needed to improve tenderness and texture of larger muscle chunks that may be incorporated in restructured muscle foods.…”
Section: Introductionmentioning
confidence: 99%